“Alem de vestir as calças do marido, ela tem que continuar de vestido” (in addition to wearing the husband’s pants, she needs to wear the dress): the process of recovery from alcohol dependency among northeast Brazilian couples - Barros Abreu Gomes, Patricia Cristina Monteiro De (Kansas State University, 2015)
The purpose of this study is to expand our understanding of alcohol dependency and its recovery in Northeast Brazil by exploring the lived experience of this disorder and its recovery process among couples whose husbands are seeking treatment for alcohol dependency. Culturally specific values such as patriarchy and gender roles were explored to gain insight into the recovery process. Findings from in-depth interviews conducted with couples and mental health professionals indicated that wives had a major role in the recovery process but were not included in the treatment process. Wives are expected to wait and temporarily “wear the pants” while husbands attend to their personal problems in treatment. Wives were viewed as a major support to husbands in treatment as well as the “stone in the middle of the road” that obstructed progress. The cultural values and gender norms appear to play a major role in how alcohol dependency is managed within the couple system and by mental health professionals. The use of metaphors to externalize problems and religious scripts helped couples cope. Clinical implications for systemic treatment and research implications are discussed.
In addition to wearing the husband's pants, she needs to wear the dress
Keywords: Alcohol dependency; Couples; Northeast Brazil; Patriarchy; Gender roles; Gender Studies (0733); Individual & Family Studies (0628); Latin American Studies (0550)